Crash kinematics and injury criteria validation for a deformable hybrid vehicle model - Venkatason, Kausalyah; Shasthri, Sevaguru; Abdullah, Kassim Abdulrahman; Idres, Moumen; Shah, Qasim Hussain; Wong, Sha Voon (Trans Tech Publications Ltd., Switzerland, 2013)
Pedestrians are vulnerable road users who are at high risks in a road traffic collision with motor vehicles. A large number are getting killed in traffic accidents each year, the majority of them being children and senior citizens. During impact with an automobile, pedestrians suffer multiple impacts with the bumper, hood and windscreen. Fatality is seen mostly due to the head injuries obtained by the pedestrians. Thus this paper aims to introduce the development and validation of a simplified hybrid vehicle front end profile for the mitigation of head injury. The vehicle model is represented by a multi body windscreen and finite element cowl, hood and bumper. A two step validation procedure is performed, firstly the crash kinematics validation to determine the overall kinematics and fall pattern of the pedestrian during impact. Secondly, the hybrid vehicle model is tested against the pedestrian injury criteria values for pertinent body parts namely the neck, sternum, lumbar, femur and tibia. The hybrid vehicle model is made to impact an adult human dummy model obtained from TNO (TASS Netherlands). The injury criterias are reprensented through the Head Injury Criteria (HIC), neck compression force, sternum and tibia accelerations and lumbar and femur bending moments. The simulation results were compared to the experimental values and a good correlation was achieved.